Future jazz - Mandel, Howard (Oxford Univ. Press, 1999)
In a series of vividly drawn portraits and intimate, in-depth interviews with musicians, composers, improvisers, and music business entrepreneurs, Mandel captures the vitality and passion of the modern jazz scene from the 1970s to the present. The most celebrated jazz stylists of recent years have been the so-called Young Lions, and Mandel includes an exclusive three part interview with the Lion King himself, Wynton Marsalis, who relates his background, philosophy of jazz, and pointed opinions on current music. But most of Future Jazz focuses on other trend-setters, tracing the development of new jazz communities (including Chicago's AACM, St. Louis's BAG, and New York's M Base Collective), groups from the Art Ensemble of Chicago to John Zorn's Masada, and major figures incluDing Gen Allen, Joe Lovano, David Murray, Henry Threadgill, and Cassandra Wilson.